2019
DOI: 10.1111/jth.14526
|View full text |Cite
|
Sign up to set email alerts
|

Topical tranexamic acid inhibits fibrinolysis more effectively when formulated with self‐propelling particles

Abstract: Background Endogenous fibrinolytic activation contributes to coagulopathy and mortality after trauma. Administering tranexamic acid (TXA), an antifibrinolytic agent, is one strategy to reduce bleeding; however, it must be given soon after injury to be effective and minimize adverse effects. Administering TXA topically to a wound site would decrease the time to treatment and could enable both local and systemic delivery if a suitable formulation existed to deliver the drug deep into wounds adequately. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…17 In addition, SPTP managed nasal bleeding in a sheep model without thrombosis or pulmonary embolism for up to 15 days postrecovery. 20 Self-propelling thrombin-containing powder appeared safe in this acute study and has been shown to be safe previously in multiple models, [17][18][19][20][21][22] but the long-term impact of SPTP on animals needs to be evaluated. This includes the breakdown of residual SPTP, which is expected to occur within several days, and evaluating its potential for forming adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…17 In addition, SPTP managed nasal bleeding in a sheep model without thrombosis or pulmonary embolism for up to 15 days postrecovery. 20 Self-propelling thrombin-containing powder appeared safe in this acute study and has been shown to be safe previously in multiple models, [17][18][19][20][21][22] but the long-term impact of SPTP on animals needs to be evaluated. This includes the breakdown of residual SPTP, which is expected to occur within several days, and evaluating its potential for forming adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…1). In previous studies, our group has shown that SPTP halted multiple lethal femoral artery and carotid hemorrhages in pigs and sheep, respectively [10][11][12][13].…”
Section: Introductionmentioning
confidence: 90%
“…The follow-up in vitro clot lysis assays verified that the self-propelling TXA particles alone could enhance clot retention in hyperfibrinolytic plasma deficient of α2-AP, an endogenous plasmin inhibitor, even without loading thrombin. 37 The particles may be useful in treating intraoperative internal bleeding, such as in the uterus, sinus, and gastrointestinal tract, where traditional topical agents cannot reachable. Moreover, given that CaCO 3 microparticles can absorb biomolecules nonspecifically, the self-propelled vehicle is ideal for drug delivery in complex vascular geometries with the assistance of intravascular catheters.…”
Section: Currently Developed Hemostatic Materials For Coagulopathymentioning
confidence: 99%